Nanoparticles and antigen-specific T-cell therapeutics: a comprehensive study on uptake and release. (April 2015) - Zupke, Oliver; Distler, Eva; Jürchott, Anna; Paiphansiri, Umaporn; Dass, Martin; Thomas, Simone; Hartwig, Udo F; Theobald, Matthias; Landfester, Katharina; Mailänder, Volker; Herr, Wolfgang
Aim: T lymphocytes are used as cellular therapeutics in many disease entities including cancer. We investigated the uptake and retention of nanoparticles (NPs) by these nonphagocytic cells.Materials & methods: Uptake, release and toxicity of various polymeric NP preparations were analyzed by flow cytometry, confocal laser scanning microscopy and transmission electron microscopy. T-cell effector functions were measured using IFN-γ-ELISPOT and 51 Chromium-release assays.Results: Amino-functionalized NPs were efficiently ingested by antigen-specific T cells without adversely influencing effector functions. NPs were stored in membrane-surrounded vesicles, with major proportions released extracellularly during 24 h.Conclusion: Amino-functionalized polymeric NPs are efficiently taken up by human T cells and could be used to design nanocarriers for direct access and manipulation of antigen-specific T cells in vivo .